TikTok for environmental care among engineering students - Violeta Leonor (2025)
The present research aimed to establish whether the dissemination of content on TikTok contributes to environmental care in engineering students. Regarding the method, it was quantitative in approach, quasi-experimental design and explanatory level with an intervention, which was the development and publication on TikTok of environmental care content. The sample consisted of industrial and agro-industrial engineering students, who were given a pre-test and after the intervention a post-test, using a 20-question questionnaire. The non-parametric Wilcoxon hypothesis test statistic confirmed the expected effects with a significance (p=0.000) allowing to conclude that the content developed and published on TikTok strengthens the environmental care of engineering students. In addition, the preparation of TikTok showed high motivation, creativity, collaborative work and ethical attitude when citing sources.